2000
DOI: 10.1088/0031-9155/45/7/316
|View full text |Cite
|
Sign up to set email alerts
|

Fracture mechanics model of stone comminution in ESWL and implications for tissue damage

Abstract: Abstract. Focused shock waves administered during extracorporeal shock-wave lithotripsy (ESWL) cause stone fragmentation. The process of stone fragmentation is described in terms of a dynamic fracture process. As is characteristic of all brittle materials, fragmentation requires nucleation, growth and coalescence of flaws, caused by a tensile or shear stress. The mechanisms, operative in the stone, inducing these stresses have been identified as spall and compressioninduced tensile microcracks, nucleating at p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
68
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(72 citation statements)
references
References 27 publications
1
68
0
3
Order By: Relevance
“…Many proposed mechanisms, such as spallation (Lubock, 1989), geometric superfocusing (Gracewski et al, 1993;Xi and Zhong, 2001), circumferential squeezing (Eisenmenger, 2001), and shear-induced failure (Xi and Zhong, 2001;Cleveland and Sapozhnikov, 2005;Sapozhnikov et al, 2007) were demonstrated during the fragmentation process in the early stage of SWL, when the stones are of sufficient size to favor the development of large stress concentrations. Other proposed mechanisms, such as dynamic fatigue (Lokhandwalla and Sturtevant, 2000) and cavitation (Coleman et al, 1987;Sass et al, 1991;Philipp and Lauterborn, 1998), describe processes that influence stone fragmentation throughout the entire course of SWL. Despite previous efforts, a disconnection still exists between the proposed mechanisms and the lithotripter shock wave (LSW) parameters that drive the stone fracture processes in SWL (Cleveland and McAteer, 2007;Sapozhnikov et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many proposed mechanisms, such as spallation (Lubock, 1989), geometric superfocusing (Gracewski et al, 1993;Xi and Zhong, 2001), circumferential squeezing (Eisenmenger, 2001), and shear-induced failure (Xi and Zhong, 2001;Cleveland and Sapozhnikov, 2005;Sapozhnikov et al, 2007) were demonstrated during the fragmentation process in the early stage of SWL, when the stones are of sufficient size to favor the development of large stress concentrations. Other proposed mechanisms, such as dynamic fatigue (Lokhandwalla and Sturtevant, 2000) and cavitation (Coleman et al, 1987;Sass et al, 1991;Philipp and Lauterborn, 1998), describe processes that influence stone fragmentation throughout the entire course of SWL. Despite previous efforts, a disconnection still exists between the proposed mechanisms and the lithotripter shock wave (LSW) parameters that drive the stone fracture processes in SWL (Cleveland and McAteer, 2007;Sapozhnikov et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the overall process of stone fragmentation in SWL is best described by the concept of dynamic fatigue (Lokhandwalla and Sturtevant, 2000). Briefly, under transient loading produced by LSW-generated stress waves and/or cavitation bubble collapse, fracture is facilitated by the opening of pre-existing microcracks (or flaws) and their a) Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Breakage tends to be gradual and stones fail by a process of fatigue due to repetitive stress 8,9. Shock waves create microcracks that progressively lengthen and expand until failure occurs.…”
Section: How Shock Waves Break Stones and Damage Tissuementioning
confidence: 99%
“…12,13 Although mechanical stress generated by the incident SW causes the initial disintegration of the stone, cavitation is a necessary component for efficient fragmentation, and particularly for producing fine passable fragments (<2 mm). 13 The effect of cavitation on the fragmentation process is thought to be primarily through erosion on the stone surface, but it may also help in the formation of crack lines through which damage is spread from the surface into the bulk of the stone.…”
Section: Introductionmentioning
confidence: 99%